The sweet symphony of N-glycans in myeloid malignancies - Sanmartín-Martínez, Javier; Wiersma, Valerie R.; Marneth, Anna E. (Frontiers in Hematology, 2024)
Although the involvement of glycan structures in diseases has long been recognized, their detailed and high-throughput investigation has only recently been made possible due to technological advancements. For this reason, glycosylation is a generally understudied phenomenon, however it could provide critical information on the pathobiology of many disorders by virtue of its widespread abundance and critical role in protein function. Here, we focus on myeloid malignancies, conditions for which the survival rates are often poor and curative therapeutic options are generally limited. We review the current literature on (1) N-glycosylation of major hematopoietic growth receptors found mutated in myeloid malignancies, (2) chemoresistance through intracellular glycan-related processes, and (3) mechanisms by which altered N-glycosylation contributes to interactions between myeloid blasts and bone marrow stromal cells leading to niche hijacking. For each topic, we describe the related pathobiology and its (potential) clinical implications. The combination of glycoproteomic and genomic information is expected to result in a deeper molecular understanding of the pathobiology of these diseases, which could subsequently be used for improving prognostication and therapeutic strategies.